A study comparing videocapillaroscopy and dermoscopy in the assessment of nailfold capillaries in patients with systemic sclerosis–spectrum disorders. (6th March 2015) - Hughes, Michael; Moore, Tonia; O'Leary, Neil; Tracey, Andrew; Ennis, Holly; Dinsdale, Graham; Murray, Andrea; Roberts, Christopher; Herrick, Ariane L.
Abstract : Objectives. Nailfold videocapillaroscopy (NVC), the current gold standard for detection of capillary abnormalities suggestive of an SSc-spectrum disorder, is not widely available: a key question is whether lower-magnification, easy-to-use dermoscopy compares favourably. This is especially relevant given the inclusion of capillaroscopic abnormality within the 2013 classification criteria for SSc. Our objectives were to examine the ability to classify capillaries and to evaluate abnormality (severity), by both NVC and dermoscopy, to determine whether these differ between general and specialist rheumatologists, and to compare intra- and interrater reliability of both techniques. Methods. NVC and dermoscopy images were acquired from all 10 nailbeds of 32 subjects with a range of capillary abnormalities. Images were graded (using a web-based interface) on a 0–3 scale of severity: normal (0), mildly (1), definitely (2) and grossly abnormal (3), and an unclassifiable category. Raters graded images from four subjects (40 nailbeds) using each technique, with five repeated images to estimate intrarater reliability. Results. Forty-eight rheumatologists from 12 countries participated in the study (22 generalists, 26 specialists). While most images could be graded by both techniques, more were graded by NVC (84% vs 70%) and were systematically scored higher by NVC (mean difference 0.43 between the ratings). Agreement between the techniques was moderate. Intra- and interrater reliability were comparable for the two techniques in the classifiability of images and the grading of severity. Conclusion. Our results suggest that dermoscopy is comparable to NVC, although NVC images were more likely to be classifiable and were graded more severely.